Model Laporan Keuangan Sederhana Dengan Menggunakan Aplikasi Android Akuntansi UKM Pada UKM di Kabupaten Brebes - Nurul Mahmudah; Yusri Anis Faidah (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2022)
The more advanced development of Indonesia is expected to be in line with the existence of economic development in terms of small micro and medium enterprises. This cannot be denied by the growing development of various types of small and medium enterprises in Indonesia, especially in Central Java. One of many government's efforts is to increase income in that aim to improve the welfare of society, the role of UKM is very much needed with the development of UKM in Central Java, especially in Brebes district. It is proving that the domestic market share ranging from low to medium-sized economies can be absorbed. One of the problems faced by UKM is preparing simple financial reports. It is because UKM is required to be able to understand simple financial reports systematically, the existence of an android application model "UKM Accounting" is able to help UKM problems in preparing simple financial reports. Therefore, this study is related to the model and application of the android application "UKM Accounting" which is used in compiling simple financial reports on UKM in Brebes Regency. The purpose of this study is to apply a simple financial reporting model using the android application "UKM accounting" for UKM in Brebes Regency. The subjects in this study were UKM in Brebes Regency. This study used descriptive analysis with a qualitative approach obtained from observations and interviews with UKM in Brebes Regency. The collected data were interpreted in the application of a simple financial reporting model using the android application "UKM Accounting" which is used by UKM in preparing financial reports.